Is there a Middle East? : the evolution of a geopolitical concept - Bonine, Michael E., 1942-; Amanat, Abbas; Gasper, Michael Ezekiel, 1963- (Stanford University Press, 2012)
Is the idea of the "Middle East" simply a geopolitical construct conceived by the West to serve particular strategic and economic interests-or can we identify geographical, historical, cultural, and political patterns to indicate some sort of internal coherence to this label? While the term has achieved common usage, no one studying the region has yet addressed whether this conceptualization has real meaning-and then articulated what and where the Middle East is, or is not. This volume fills the void, offering a diverse set of voices-from political and cultural historians, to social scientists.